Graftização de anidrido maleico em polipropileno, por extrusão reativa, na presença de nanopartículas: estudo de reação e monitoramento in-line - Muñoz, Pablo Andrés Riveros (Universidade Federal de São Carlos, 2014)
The grafting reaction of maleic anhydride onto polypropylene by reactive extrusion, in presence of nanoclay, was studied. The organoclay (Cloisite 20A) was used as support for dicumyl peroxide (DCP), and different amounts of clay were used. The increment in the clay amount leads to reduction in the reaction rates, because it hinders the peroxide release, once organoclay absorbs partially the peroxide. Changes in the reaction mechanisms, in presence and absence of clay, were performed in a Haake internal mixing chamber, between 1 and 7 min of reaction. The results showed changes in the number, and length of maleic anhydride grafting, and in the molar mass. The reactive extrusion of polypropylene with maleic anhydride was studied based in central composite experimental design, using as factors the maleic anhydride and dicumyl peroxide concentrations. The experimental design was analyzed by ANOVA and shows that the increment in clay, used as peroxide support, leads to decrease in the grafting reaction of short succinic groups, by the introduction of long succinic groups, because its concentration increases the maleic anhydride homopolymerization. In the same way the increase in maleic anhydride concentration leads to decrease in the PP grafting level, because the maleic anhydride homopolimerization is increased, decreasing the reaction between polymer and monomer. The in-line monitoring of the reactive extrusion showed a good correlation between the light absorption measured and the formation of secondary reaction products, lately identified off-line as poli(maleic anhydride).
Keywords: Materiais; Extrusão reativa; Montmorilonita; Cromatografia; Polipropileno; Reactive extrusion; In-line monitoring; Polypropylene; Montmorillonite; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA